Comparative antioxidant activity, proteolysis and in vitro α-amylase and α-glucosidase inhibition of allium sativum-yogurts made from cow and camel milk - Shori, A.B.; Baba, A.S.H. (2011)
The presence of extract of plant with medicinal properties during milk fermentation could enhance the therapeutical values of yogurt. In the present study, the effects of Allium sativum on the changes in post-acidification, total phenolic content (TPC), proteolysis by o-phthaldialdehyde (OPA) assay, antioxidant activity by (1,1-diphenyl-2-picrylhydrazyl radical (DPPH) inhibition) and capacity to inhibit in vitro α-amylase and α-glucosidase activities in cow or camel milk yogurt (MY) during 21 day refrigerated storage were investigated. The presence of A. sativum enhanced more pH reduction for camel-MY than for cow-MY compared to their respective controls during storage. The reverse was true for total titratable acid. TPC in camel-MY was higher (p < 0.05) than that in cow-MY. The presence of A. sativum in cow- and camel-MYs elevated (p < 0.05) the TPC, but these changed little during storage. Antioxidant activities (18-38% DPPH inhibition) were not different in both types of yogurts, either in the absence or in the presence of A. sativum. However, camel-MY had an increase (p < 0.05) in antioxidant activities (49-65%) during 7-21 days of storage. OPA values on day 0 was higher for camel-MY (368.2 ± 14.8 mg/g) than for cow-MY (80.1 ± 3.2 mg/g). The presence of A. sativum increased OPA values more for cow-MY than for camel-MY (3.0- and 1.3-folds, respectively). Higher inhibition (p < 0.05) of α-amylase by camel-MY compared to cow-MY occurred whereas α-glucosidase inhibition by cow-MY reduced (p < 0.05) as a result of refrigeration greater than 7 days. In general, the addition of A. sativum caused more antioxidant activities, proteolysis and enzymes (α-amylase and α-glucosidase) inhibition in camel-MY than in cow-MY. © 2011.